Promoting Critical Thinking in Junior High School: Challenges and Practices From EFL Teachers - Mufidati, Afifah; Retnaningdyah, Pratiwi; Nugroho, Him'mawan Adi (EduInovasi: Journal of Basic Educational Studies, 2024)
Critical thinking skills is highly encouraged by educators for their students to challenge their students to achieve critical values, the sense of creativity, and the requirement of high order thinking. The purpose of this study is to explore how English teachers as a foreign language promote critical thinking skills in junior high school and the barriers they face. This study adopts an exploratory, descriptive, and qualitative research design. Barriers included student and parental attitudes, teacher and institutional issues, and cultural constraints. Participants noted a lack of cultural value for critical thinking. Recommendations emerged, such as tailored teacher training programs, a shift towards critical thinking in curricula, pedagogical support emphasizing critical thinking, and enriched textbooks with activities encouraging critical thought. The novelty of this research lies in its focus on English language teaching from the perspective of teachers' perceptions, particularly regarding the role of textbooks and the enhancement of critical thinking skills among students.